Occupational socioeconomic risk associations for head and neck cancer in Europe and South America: individual participant data analysis of pooled case–control studies within the INHANCE Consortium. Issue 8 (23rd February 2021) - Conway, David I; Hovanec, Jan; Ahrens, Wolfgang; Ross, Alastair; Holcatova, Ivana; Lagiou, Pagona; Serraino, Diego; Canova, Cristina; Richiardi, Lorenzo; Healy, Claire; Kjaerheim, Kristina; Macfarlane, Gary J; et al.
Abstract : Background: The association between socioeconomic disadvantage (low education and/or income) and head and neck cancer is well established, with smoking and alcohol consumption explaining up to three-quarters of the risk. We aimed to investigate the nature of and explanations for head and neck cancer risk associated with occupational socioeconomic prestige (a perceptual measure of psychosocial status), occupational socioeconomic position and manual-work experience, and to assess the potential explanatory role of occupational exposures. Methods: Pooled analysis included 5818 patients with head and neck cancer (and 7326 control participants) from five studies in Europe and South America. Lifetime job histories were coded to: (1) occupational social prestige—Treiman's Standard International Occupational Prestige Scale (SIOPS); (2) occupational socioeconomic position—International Socio-Economic Index (ISEI); and (3) manual/non-manual jobs. Results: For the longest held job, adjusting for smoking, alcohol and nature of occupation, increased head and neck cancer risk estimates were observed for low SIOPS OR=1.88 (95% CI: 1.64 to 2.17), low ISEI OR=1.74 (95% CI: 1.51 to 1.99) and manual occupations OR=1.49 (95% CI: 1.35 to 1.64). Following mutual adjustment by socioeconomic exposures, risk associated with low SIOPS remained OR=1.59 (95% CI: 1.30 to 1.94). Conclusions: These findings indicate that low occupational socioeconomic prestige, position and manual work are associated with head and neck cancer, and such risks are only partly explained by smoking, alcohol and occupational exposures. Perceptual occupational psychosocial status (SIOPS) appears to be the strongest socioeconomic factor, relative to socioeconomic position and manual/non-manual work.